Prevalence and reasons influenced medication non‑adherence among diabetes patients: A mixed‑method study - Abdullah, Nor Fadhilah; Lee, Khuan; Cheong, Ai Theng; Sowtali, Siti Noorkhairina (Springer Nature, 2022)
Objectives This study aimed to identify the prevalence of medication non-adherence (MNA) and to explore the reasons that influenced MNA among diabetes patients. Design This study used the explanatory mixed-method design. Phase one comprised of a cross-sectional study followed by phase two of a qualitative study. Setting This study took place at two public hospitals in the Klang Valley, Malaysia. Participants About 427 diabetes patients were recruited and 399 of them completed the study. The inclusion criteria were those with age more than 18 years and above, Malaysian citizen, able to understand Malay or English, and were diagnosed with diabetes mellitus for more than one year. The exclusion criteria were those with an intellectual disability and pregnant women. Phase two involved 12 participants recruited from non-adherent patients in phase one of the study. Results About 46.6% of the patients failed to adhere to the medication. Malays (OR: 1.66, 95%CI: 1.09 to 2.51, p = 0.017), single/widow or divorced (OR: 1.79, 95%CI: 1.05 to 3.05, p = 0.031) and poor HbA1c (OR: 2.57, 95% CI: 1.61 to 4.10, p = < 0.01) were associated with medication non-adherence. Five main categories emerged as the reasons for medication non-adherence, including perceived benefit of Complementary and Alternative medicine, attitude towards drawback of western medication, poor healthcare providers and patients' relationship, undesirable emotional response towards medication intake, as well as restraints in daily routine and cognitive function. Conclusions There are many reasons for patients' non-adherence to their anti-diabetes medication. These findings are impor-tant in identifying the factors that influenced non-adherence to recommend reliable patient-centred care strategies in improv-ing medication non-adherence among patients with diabetes.